Preterm delivery is associated with long-term risk of maternal renal disease. (13th November 2019) - Barrett, P; McCarthy, F P; Evans, M; Kublickas, M; Perry, I J; Stenvinkel, P; Kublickiene, K; Khashan, A S
Abstract: Background: Preterm delivery is an independent risk factor for maternal cardiovascular disease. Little is known about the association between preterm delivery and maternal renal function, and whether any association is independent of preeclampsia or intra-uterine growth restriction. This study aimed to examine the association between gestational age and long-term maternal chronic kidney disease (CKD) and end-stage kidney disease (ESKD). Methods: Using data from the Swedish Medical Birth Register, singleton live births from 1973-2012 were identified and linked to data from the Swedish Renal Register and National Patient Register (up to 2013). Women with pre-pregnancy CKD/ESKD, cardiovascular disease, diabetes, hypertension, systemic lupus erythematosus were excluded. Gestational age at delivery was the main exposure, treated as a time-dependent variable. Primary outcomes were maternal CKD or ESKD. Cox regression was used, adjusting for maternal age, year of delivery, country of origin, education, parity, interpregnancy interval, smoking, BMI, gestational diabetes. Models were stratified by exposure to preeclampsia or small for gestational age (SGA). Results: There were 3, 847, 694 pregnancies among 1, 990, 273 unique women. Nine percent of women (n = 172, 915) had at least one preterm delivery (<37 weeks). Exposure to preterm delivery was associated with higher risk of CKD (aHR 1.48, 95%CI 1.41-1.54) and ESKD (aHR 2.52, 95%CI 2.17-2.92). Earlier gestational age at delivery was associated with increasing risk of CKD and ESKD. Women with spontaneous preterm delivery were at higher risk of CKD (vs. normal term, aHR 1.33, 95% CI 1.26-1.40) and ESKD (aHR 2.02, 95%CI 1.69-2.40) independently of preeclampsia/SGA. Associations persisted after excluding women who developed postpartum cardiovascular disease, hypertension or diabetes. Conclusions: Women who gave birth at earlier gestation were at higher risk of later CKD and ESKD. This association persisted independently of preeclampsia and SGA. Key messages: Preterm delivery is an independent predictor of long-term maternal renal disease. Obstetric history should be considered as part of overall risk stratification for chronic kidney disease in women.